RESULT OF USING ENCOURAGE BOOK OF VERSE STORY FOR PRONUNCIATION AND SKIMMING SKILL DEVELOPMENT IN THAI STUDIES SUBJECT GROUP OF ELEMENTARY PUPILS 1 (ES 1) - MueangJai, Saengdao (Journal of Social Science and Cultural, 2024)
This research aims aims to. The objective of the research is : 1) Creating and finding out an efficiency of encourage book of verse story for pronunciation and skimming skill development in Thai Studies Subject Group of Elementary Pupils 1 (ES 1) Mueang Chiangrai Nursery School (Sansai Ratdarunnanukroh), 2) Studying academic achievement on pronunciation and skimming skill development before and after using the created encourage book of verse story Mueang Chiangrai Nursery School (Sansai Ratdarunnanukroh); 3) Studying satisfaction in the created encourage book of verse story of Elementary Pupils 1 (ES 1) students Mueang Chiangrai Nursery School (Sansai Ratdarunnanukroh) by using technique of Simple Random Sampling and a classroom random unit. The 18 representative samples in Elementary Pupils 1/2 students, Mueang Chiangrai Nursery School (Sansai Ratdarunnanukroh) were used for this study, by Using the classroom as the randomization unit. The research tools were 1) The 9 created encourage books of verse story, 2) academic achievement tests on pronunciation and skimming skill development, 3) satisfaction questionnaires for Elementary Pupils 1 (ES 1) students; 4) The 20 Learning management plans were conducted for this study. Percentage, mean, standard deviation and t-test were used for data analysis. Table of กdata and essay were used for presentation. Result showed that; 1) Efficiency of the 9 created encourage books of verse story for Elementary Pupils 1 (ES 1) students was found equal to 85.49/83.95, 2) Significant difference was found in academic achievement for skimming skill development after using the created encourage books of verse story at the confidence level 0.05, that the advance score was 35.00%. 3) The high satisfied questionnaires for Elementary Pupils 1 (ES 1) students level ( = 2.93, S.D. = 0.18).